AN ANALYSIS OF LEVEL QUESTIONS IN READING EXERCISES OF STUDENTS ENGLISH TEXTBOOK GRADE X BASED ON REVISED BLOOM’S TAXONOMY - Rizky Adryati; Masitowarni Siregar; Nora Ronita Dewi (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2019)
The objective of this research was to analyze the level of questions in reading exercises of students English Textbook grade X based on Revision Bloom’s Taxonomy. This study would be a descriptive study, which analyze the reading exercises in English for Senior High School Grade X textbook published by Masmedia in 2017 based on the cognitive domain of Bloom’s Taxonomy. The dominant design of this research would be Qualitative method. The data would be collected by using checklist. For collecting data there are four steps, selecting, classifying, coding and the last, the result of the checklist show the percentage of reading question which are referring to the cognitive domain. The findings of this research was the questions in the textbook did not cover all of the cognitive levels which consist of remembering, understanding, applying, analyzing, evaluating and creating. There was no question belong to creating. Cognitive levels found in the textbook were as follows: remembering got 75 questions out of 115 questions or 65,21%. Understanding level question obtained 14 questions out of 115 questions or 12,17%. Applying level obtained 1 items out of 115 questions or 0.86%. Analyzing level obtained 21 questions out of 115 questions or 18,26%. Evaluating level obtained 2 items out of 115 questions or 1,7% and there was 2 questions belong to creating level out of 115 questions that put elements together to form a coherent or functional whole; reorganize elements into a new pattern or structure. Key words: Revision Bloom’s Taxonomy, Reading Exercises, English Textbook